If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(5m + 9) = 34 Reorder the terms: 7(9 + 5m) = 34 (9 * 7 + 5m * 7) = 34 (63 + 35m) = 34 Solving 63 + 35m = 34 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-63' to each side of the equation. 63 + -63 + 35m = 34 + -63 Combine like terms: 63 + -63 = 0 0 + 35m = 34 + -63 35m = 34 + -63 Combine like terms: 34 + -63 = -29 35m = -29 Divide each side by '35'. m = -0.8285714286 Simplifying m = -0.8285714286
| 8-x=4y | | 1/9^1-3x^2 | | 1-3(2)=0 | | 1-2(2)= | | 4x+689%133=14795 | | y=abs(ln(abs(x))) | | 979+485+379= | | -2(t-2)+6t=9t-6 | | w^2-14+13=0 | | -2(t-1)+4t=5t-9 | | f(x)=3x^2+7x+8 | | (7+v)(2v+9)=0 | | -112=8b(2-2a) | | 7(x-4)=9 | | 15mn^3-25m^2-15mn^2= | | y=-16x^2+96x-128 | | 61=x*y+z | | f(x)=x^3+3x^2*5x+4 | | 7(2p+3)-8=6p+39 | | 3w-3=3x+6 | | y-200=8x | | 0.1x^2+2x=50 | | 3x^2-9=-6 | | y=3cos(4x^2) | | x^45/x^2-1 | | 8x+7=10-5 | | 7x-4=4x | | 2x^2+2+5x=0 | | -nm^4/-3m^2n^-1 | | ln(14/a*x^2*-2x)*-2 | | x^2-(k+1)x+2k+3=0 | | -3(1/3)=1/2g |